Investigating the early implementation of MFRS 136 disclosure among top 50 firms in Malaysia - Aisyah Abdul Rahman; Ahmad Syubaili Mohamed; Nur Hidayah Laili; Khairil Faizal Khairi (Penerbit Universiti Kebangsaan Malaysia, 2017)
The highly prescriptive and technical provisions of MFRS 136 – Impairment of Assets represent a very considerable variationfrom past practices. This in turn raises questions about the span to which Malaysian businesses and their auditors have fared during the method of transition to a convoluted new reporting regime. Malaysia through Malaysian Accounting Standards Board (MASB) made the requirements of the MFRS 136 - Impairment of Assets mandatory progressively since 1